EXPERIMENTAL SYUDY OF MIXED CONVECTION HEAT TRANSFER FOR A THERMALLY DEVELOPING AIR FLOW (Journal of Engineering, 2005)
The investigation-included experiments were conducted to investigate the local and average mixedconvection heat transfer coefficient for thermally developing and fully developed hydrodynamically laminar airflow in an inclined annulus. The experimental setup, using an aluminum annulus having a radius ratio of (0.41) and the inner tube with a heated length of (0.85m) with constant wall heat flux boundary conditions. The investigation covered Reynolds number range from (332 to 1128) and heat flux varied from (82w/m² to 545w/m2). The air is developed hydrodynamically by using the entrance section annulus (calming section) having the same inner and outer diameter as a test section but with variable lengths. The entrance sections included a long calming section with a length of 90 cm (L/D 20.93) and short calming section with lengths of 60 cm (L/D=13.95). The results obtained represent the temperature distribution along the inner tube surface, the local and average Nusselt number distributions with the dimensionless axial distance (Z). For all annulus orientations and all entrance sections, the results show an increase in the Nusselt number values as the heat flux increases and as the aagle of the inclination moves from the vertical to the horizontal position. A comparison was made between the experimental results and the available previous work of Mataira, D. and Subba Raju, K. (1975), for the local Nusselt number distribution with the dimensionless axial distance (Z). The results obtained showed a good agreement and has the same trend that obtained in the previous work.